A comparative assessment of the fatty acid profiles and antioxidant status of supermarket eggs. (7th August 2015) - Gaffney, Mark; O'Rourke, Rachel; Taylor-Pickard, Jules; Murphy, Richard
Summary: Nutrient deposition in eggs is largely dictated by the dietary composition of laying hen feed, particularly in terms of specific fatty acids and antioxidants. In the present study, the nutritional quality of a range of commercially available egg varieties, marketed as omega-3 enriched; corn-fed; free range and standard caged, were assessed by determining fatty acid profiles and antioxidant status. Across each egg variety, significant differences were observed in key fatty acids such as palmitic, oleic, linoleic, alpha-linolenic and docosahexaenoic acid (DHA) (P ≤ 0.05). Egg yolks enriched with a stated dietary source of omega-3 fatty acid DHA were shown to have significantly improved levels of DHA (P ≤ 0.05), approximately 4.5-fold higher than standard caged eggs. Compared with free range, corn fed and caged, eggs from diets enriched with a source of omega-3 were shown to have considerably altered omega-6: omega-3 ratios, amounting to 1.5–2.1 fold reductions. Yolk antioxidant activity was improved for omega-3 enriched eggs, particularly in hexane fractionated samples. The inclusion of omega-3 fatty acids to the diet resulted in eggs with improved DHA contents and antioxidant status, highlighting the importance of poultry diet composition for egg nutritional quality.